Cognitive Trajectories Following Acute Infection in Older Patients With and Without Cognitive Impairment: An 1-Year Follow-Up Study - Silva, Ana Rita; Regueira, Patrícia; Cardoso, Ana Luísa; Baldeiras, Inês; Santana, Isabel; Cerejeira, Joaquim (Frontiers in Psychiatry, 2021)
Introduction: Dementia is a known risk factor for both delirium and acute systemic infections which may also play a significant role in promoting or accelerating neurodegenerative disease. Infections are both the main causes of hospitalization of dementia patients and can be a major precipitant of delirium but currently it is not possible to predict the risk of cognitive decline in older patients exposed to acute infection. Objectives: We aimed to determine the level of cognitive change at one-year follow up in individuals with different patterns of cognitive function (dementia, delirium, delirium superimposed on dementia) at the time of their hospitalization due to a systemic infection and to correlate these cognitive patterns with clinical status variables. Methods - We recruited 53 hospitalized geriatric patients with a systemic infection, and we collected 12-months follow up data for 34 patients. These patients were classified in four groups: no cognitive impairment (controls - C), delirium only (D), dementia only (Dem), and delirium superimposed to dementia (DD). Cognitive performance was measured by change in score on the Montreal Cognitive Assessment (MoCA) and delirium was identified using Confusion Assessment Measure (CAM). We examined performance on the MOCA in the first year after hospitalization, controlling for demographic characteristics, coexisting medical conditions, and type of infection. Results - For the 34 patients to whom follow-up data was available, delirium presence in individuals with prior dementia (DD group) was associated with a negative mean change score of 3-point (p<.02) at one year follow up, whereas dementia patients without delirium had a mean change score of 1.5-point lower at 12-months (p=.04), when comparing follow-up and baseline MoCA scores. Cognitively healthy patients did not significantly decrease their MoCA score at follow-up (p=.15). MoCA and NPI scores during hospitalization were significantly correlated with the level of cognitive decline in the four groups (r=.658, p<.01 and r=.439, p=.02, respectively). Conclusions: Premorbid dementia and delirium superimposed on dementia during hospitalization in older patients with acute infections predict cognitive decline at one year following admission. Taken together, our findings suggest a pathophysiological interaction between acute infection, cognitive impairment and delirium.